STRATEGI MENUMBUHKAN KREATIVITAS PESERTA DIDIK MELALUI PENDEKATAN SAINTIFIK PADA MATA PELAJARAN PANCASILA DI SEKOLAH DASAR - Rahmah, Ainu Fadilah; Maritasari, Donna Boedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the methods used by teachers to enhance students' creativity through a scientific-based approach in Pancasila lessons in fifth grade students of SDN Jurang Mangu Barat 02. In addition, this study also focuses on identifying the obstacles faced and explaining the solutions provided to overcome these problems. The method used in this study is a qualitative approach with a descriptive research type. The research subjects consisted of the principal, fifth grade teachers, and five students who were selected intentionally. Data collection was carried out using observation, interviews, and documentation techniques, while data analysis used an interactive model that included data reduction, data presentation, and conclusion drawing. Data validity was obtained through source triangulation and technique triangulation. The results of the study indicate that the methods applied by teachers to encourage student creativity include the use of Project-Based Learning (PjBL), Problem-Based Learning (PBL), discussions in diverse groups, relevant case studies, and the use of audio-visual media that have been combined with steps in the scientific approach. Some of the obstacles that emerged included limited learning resources, variations in student learning styles, low student engagement, limited learning time, and differences in student backgrounds. Solutions implemented by teachers included forming heterogeneous groups, using thought-provoking questions, maximizing technology as an alternative learning resource, and providing constructive feedback. Thus, the consistent application of a scientific approach supported by diverse learning strategies has proven effective in enhancing student creativity in Pancasila lessons at the elementary level.